Adoption of e-government services by small municipalities. Issue 2 (16th May 2019) - Chen, Yu-Che; Kim, Yunseung
Abstract : Purpose: The purpose of this paper is to fill the research gap in online information and service adoption by small public organizations. According to the US Census, small municipalities with populations of 5, 000 or less constitute 76 percent of all municipalities. Moreover, although these governments can benefit most from e-government adoption, their e-government activities are rarely studied. Design/methodology/approach: The primary data collection is a state-wide survey of small municipalities along with collecting data on websites and other government documents. The data analysis utilized logistic regression for adoption decisions. Findings: The findings suggest a distinct set of factors influencing e-government adoption by small municipalities as opposed to large ones. Moreover, management support for open access to government is critical for both e-government information and transaction services while transaction services are also driven by administrative capacity and citizen demand. Originality/value: This study is original in several ways. First, it is comprehensive in incorporating capacity and network factors along with motivation for management support. Second, it focuses on small municipalities that are important but less studied. At last, it provides a rich understanding of the distinction between information and transaction e-government services.